Direct estimation of per nucleotide and genomic deleterious mutation rates in Drosophila. - Haag-Liautard, C.; Dorris, M.; Maside, X.; Macaskill, S.; Halligan, D.L.; Charlesworth, B.; Keightley, P.D. (Nature, 2007)
Spontaneous mutations are the source of genetic variation required for evolutionary change, and are therefore important for many aspects of evolutionary biology. For example, the divergence between taxa at neutrally evolving sites in the genome is proportional to the per nucleotide mutation rate, u (ref. 1), and this can be used to date speciation events by assuming a molecular clock. The overall rate of occurrence of deleterious mutations in the genome each generation (U) appears in theories of nucleotide divergence and polymorphism, the evolution of sex and recombination, and the evolutionary consequences of inbreeding. However, estimates of U based on changes in allozymes or DNA sequences and fitness traits are discordant. Here we directly estimate u in Drosophila melanogaster by scanning 20 million bases of DNA from three sets of mutation accumulation lines by using denaturing high-performance liquid chromatography. From 37 mutation events that we detected, we obtained a mean estimate for u of 8.4 x 10(-9) per generation. Moreover, we detected significant heterogeneity in u among the three mutation-accumulation-line genotypes. By multiplying u by an estimate of the fraction of mutations that are deleterious in natural populations of Drosophila, we estimate that U is 1.2 per diploid genome. This high rate suggests that selection against deleterious mutations may have a key role in explaining patterns of genetic variation in the genome, and help to maintain recombination and sexual reproduction.